The Cerebellum under Stress: Dietary African Walnut (Tetracarpidium conophorum) Abrogates Oxidative Stress-driven Neuropathology Induced by Chronic Unpredictable Stress - Yawson, Emmanuel (My University, 2021)
Background: Consumption of a healthy diet abundant in antioxidant and anti-inflammatory phytochemicals, offers an effective and least expensive way to prevent neurodegeneration. Herein, the role of Tetracarpidium conophorum (African walnut) enriched diet in chronic stress-induced cerebellar neuropathology was investigated Methodology: Twenty-one male Wistar rats were used for this investigation. Rats were randomly assigned into three groups (A, B, and C), each consisting of 7 rats (n = 7). Group A (Control group) were fed control diet; group B rats were subjected to different chronic unpredictable stressors (CUS) + control diet for 21 days, while group C rats were subjected to CUS + Walnut-enriched diet for 21 days. Serum corticosterone levels, the expression level of antioxidant and inflammatory markers, and cytoarchitectural changes in cerebellum were assessed by enzyme-linked immunosorbent assay (ELISA) immunohistochemistry methods. Results: The walnut-enriched diet prevented astrogliosis, modulated serum corticosterone expression, and tumor necrotic factor-α in the cerebellum. The walnut-enriched diet also caused an improvement in the antioxidant profile, indicating that it suppressed chronic unpredictable stress-induced perturbations. Conclusion: Our results suggest that African walnut exerts protective effects against oxidative stress-driven dysfunction by reducing serum corticosterone levels, modulating oxidative stress pathways, and preventing neuronal morphological damage in the cerebellum.